Is it time to bet on a fashion retailer? : Valuation of INDITEX S.A. - Nguyen, Phuong Anh; Rýdlová, Barbora, 1976-; Nistorenco, Taisia; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2019)
This thesis starts with the description of a company Inditex, its core operations and its business model. The work also maps the current trends in the fashion and apparel industry in order to conduct a strategic analysis and determine factors that might influence the company’s share value. Joined by a financial analysis as well as competitors’ analysis the work ends with a valuation part where the goal is to arrive at the company’s fair market value and provide an investment recommendation.
Vedoucí práce: Barbora Rýdlová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses